Prognostic Relevance of Steroid Sulfation in Adrenocortical Carcinoma Revealed by Molecular Phenotyping Using High-Resolution Mass Spectrometry Imaging. (1st October 2019) - Sun, Na; Kunzke, Thomas; Sbiera, Silviu; Kircher, Stefan; Feuchtinger, Annette; Aichler, Michaela; Herterich, Sabine; Ronchi, Cristina L; Weigand, Isabel; Schlegel, Nicolas; Waldmann, Jens; Candida Villares Fragoso, Maria; et al.
Abstract: BACKGROUND: Adrenocortical carcinoma (ACC) is a rare tumor with variable prognosis even within the same tumor stage. Cancer-related sex hormones and their sulfated metabolites in body fluids can be used as tumor markers. The role of steroid sulfation in ACC has not yet been studied. MALDI mass spectrometry imaging (MALDI-MSI) is a novel tool for tissue-based chemical phenotyping. METHODS: We performed phenotyping of formalin-fixed, paraffin-embedded tissue samples from 72 ACC by MALDI-MSI at a metabolomics level. RESULTS: Tumoral steroid hormone metabolites—estradiol sulfate [hazard ratio (HR) 0.26; 95% CI, 0.10–0.69; P = 0.005] and estrone 3-sulfate (HR 0.22; 95% CI, 0.07–0.63; P = 0.003)—were significantly associated with prognosis in Kaplan–Meier analyses and after multivariable adjustment for age, tumor stage, and sex (HR 0.29; 95% CI, 0.11–0.79; P = 0.015 and HR 0.30; 95% CI, 0.10–0.91; P = 0.033, respectively). Expression of sulfotransferase SULT2A1 was associated with prognosis to a similar extent and was validated to be a prognostic factor in two published data sets. We discovered the presence of estradiol-17β 3, 17-disulfate (E2S2) in a subset of tumors with particularly poor overall survival. Electron microscopy revealed novel membrane-delimited organelles in only these tumors. By applying cluster analyses of metabolomic data, 3 sulfation-related phenotypes exhibited specific metabolic features unrelated to steroid metabolism. CONCLUSIONS: MALDI-MSI provides novel insights into the pathophysiology of ACC. Steroid hormone sulfation may be used for prognostication and treatment stratification. Sulfation-related metabolic reprogramming may be of relevance also in conditions beyond the rare ACC and can be directly investigated by the use of MALDI-MSI.